2022
DOI: 10.1039/d2sc03145k
|View full text |Cite
|
Sign up to set email alerts
|

Surface coverage control for dramatic enhancement of thermal CO oxidation by precise potential tuning of metal supported catalysts

Abstract: External potential control allows reactant coverage control on the catalyst, in this case to suppress excessive CO adsorption, leading to improved thermal CO oxidation performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…31,32 Additionally, when combined with in situ spectroscopies, the adsorbate coverages can be revealed and correlated to the catalyst potential and the thermal−catalytic rate. 33,34 Moreover, the mixed potential theory was proposed to elucidate redox reactions such as electroless metal plating 35 and the corrosion of surfaces, 36 and later a short-circuit electrochemical cell model has been further developed to analyze heterogeneous thermal−catalytic reactions as two coupled electrochemical half-reactions. 37−41 For example, Ryu et al found that aqueous chemical aerobic oxidation reactions could be analyzed as two half-reactions, 38 and An et al proved that such a model was also valid for aqueous hydrogenation reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Additionally, when combined with in situ spectroscopies, the adsorbate coverages can be revealed and correlated to the catalyst potential and the thermal−catalytic rate. 33,34 Moreover, the mixed potential theory was proposed to elucidate redox reactions such as electroless metal plating 35 and the corrosion of surfaces, 36 and later a short-circuit electrochemical cell model has been further developed to analyze heterogeneous thermal−catalytic reactions as two coupled electrochemical half-reactions. 37−41 For example, Ryu et al found that aqueous chemical aerobic oxidation reactions could be analyzed as two half-reactions, 38 and An et al proved that such a model was also valid for aqueous hydrogenation reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These studies reported that by utilizing a metal catalyst as the working electrode (WE) in an electrochemical system equipped with a well-defined reference electrode (RE), the catalyst potential in operando could be measured. Mathematical models were then used to analyze the catalyst potential during thermal catalysis. , Additionally, when combined with in situ spectroscopies, the adsorbate coverages can be revealed and correlated to the catalyst potential and the thermal–catalytic rate. , Moreover, the mixed potential theory was proposed to elucidate redox reactions such as electroless metal plating and the corrosion of surfaces, and later a short-circuit electrochemical cell model has been further developed to analyze heterogeneous thermal–catalytic reactions as two coupled electrochemical half-reactions. For example, Ryu et al found that aqueous chemical aerobic oxidation reactions could be analyzed as two half-reactions, and An et al proved that such a model was also valid for aqueous hydrogenation reactions . Adams et al reported the utilization of mixed potential theory for the prediction of operation potential, reactivity, and selectivity of the aqueous synthesis of H 2 O 2 from H 2 and O 2 over various Pd-based catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…With NEMCA, thermocatalytic reactions occur at an electrified interface while Faradaic processes do not contribute appreciably to the formation of products. The Fermi level of catalysts is directly controlled by an external power source without changing the catalyst structure, affording the possibility of establishing a direct correlation between the electronic state of the catalyst and the catalytic performance. Early NEMCA studies were largely conducted on high-temperature electrochemical interfaces with solid inorganic electrolytes. ,,,, Migrations of ionic species to catalytic interfaces complicate the interpretation of the effect of the applied potential on the activity. ,, Recent studies showed that electric polarization could have a significant impact on the reaction rates at close to ambient conditions in aqueous electrolytes without affecting the structure of the catalysts, highlighting the feasibility of leveraging electric polarization to isolate the impact of the Fermi level on the rate on metal-catalyzed reactions. However, the mechanistic understanding of the pathways through which electric polarization of the catalyst impacts the performance, especially the product distribution, of thermocatalytic reactions remains incomplete.…”
Section: Introductionmentioning
confidence: 99%